DIE SLAG VAN DOORNKRAAL - Nöthling, C.J. (Scientia Militaria - South African Journal of Military Studies, 2012)
Contrary to the premise that military historians tend to regard the Battle of Doornkraal as a minor skirmish of the Second Anglo-Boer War, this article expounds the view that the outcome of this brief but violent encounter had far-reaching implications. A detailed account of the events leading up to the British surprise attack on General De Wet’s commando forces at dawn on 6th November 1900 is given. As the author points out, De Wet had ample warning of his foe’s intentions: his narrow escape at Rensburgdrift was almost a full dress-rehearsal for the tragic act to be played out at Doornkraal. De Wet did not heed this warning, thereby committing perhaps the greatest tactical blunder of his military career. For the British Doornkraal was a major victory, but one for which they had to pay dearly. As things turned out, they lost a few able officers and a tailor-made opportunity to capture President M.T. Steyn and General De Wet. The Boer general swore revenge, and the British had to suffer humiliation and defeat until the end of the war.